Intracellular Localization of Nitrate Reductase in Neurospora crassa - Roldán, José M. (1982)
Nitrate reductase was localized in mycelial cells of Neurospora crassa by immunohistochemical labeling with ferritin. The enzyme is found in the cell wall-plasmalemma region and in the tonoplast membranes.